BETWEEN MOBILIZATION AND TRUST: THE TRANSFORMATION OF POLITICAL LEGITIMACY IN UKRAINE DURING THE WAR - Kononenko, Nataliia (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2025)
The article examines the institutional legitimation of political power in Ukraine during 2022–2025 under conditions of full-scale war. The study aims to assess the effectiveness of various instruments of legitimation and to test an analytical model for identifying «legitimacy gaps» between their normative significance and practical implementation. It traces the evolution of public trust – from emotional mobilization in the early stages of the war to a rationalized mode of «legitimation through survival», grounded in the state’s ability to ensure security, stability, and social justice. The paper analyzes the paradox of Ukraine’s «fighting democracy», where short-term mobilizational legitimacy facilitates swift decision-making but simultaneously exacerbates problems of institutional capacity, inclusiveness, and accountability. Empirical analysis based on expert surveys reveals significant legitimacy gaps within the parliament and government, while the presidency retains the highest level of public trust. Normative-legal and communicative mechanisms remain underutilized, generating asymmetry between societal expectations and institutional performance. The article emphasizes that wartime conditions have accelerated the concentration of power, further testing the resilience of democratic checks and balances. The research underscores that sustaining legitimacy in wartime democracies requires not only procedural adaptation but also renewal of the social contract based on mutual accountability between state and citizens. The author argues that post-war restoration of democratic legitimacy will require a shift from mobilizational governance to «managed openness», in which effectiveness is combined with transparency, accountability, and citizen participation in public administration. The proposed analytical model of legitimacy gaps offers a tool for assessing current stability and forecasting the prospects of democratic development. By integrating empirical indicators with normative benchmarks, the model contributes to a more nuanced understanding of institutional resilience under extreme conditions. It also provides a comparative framework for analyzing how wartime democracies recalibrate legitimacy mechanisms to balance survival imperatives with democratic continuity.